2014
DOI: 10.1021/ef4022637
|View full text |Cite
|
Sign up to set email alerts
|

Thixotropic Rheological Behavior of Maya Crude Oil

Abstract: Heavy oil and bitumen exhibit non-Newtonian rheological behaviors at lower temperatures. Thixotropy is one such behavior. Thixotropy affects the efficiency and length scale of mixing during blending operations and flow behaviors in pipes and pipelines following flow disruption, where it affects the pressure required to reinitiate flow. In the present work, thixotropic behaviors of Maya crude oil are explored systematically using a stress-controlled rheometer. Maya crude oil is shown to be a shear-thinning flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 33 publications
5
55
1
Order By: Relevance
“…The lowest concentration tested (10 mg/l) generates average reductions in viscosity of roughly 3%. The increasing shear rate slightly decreases the DVR benefit, which is mainly due to a change in the internal structure of the fluid (Ghannam et al, 2012;Mortazavi-Manesh and Shaw, 2014) that causes a decrease in viscosity. For this reason, the oil viscosity without NPs is lower than at low shear rates, and although the NPs have an effect at any shear rate, its performance is slightly lower.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest concentration tested (10 mg/l) generates average reductions in viscosity of roughly 3%. The increasing shear rate slightly decreases the DVR benefit, which is mainly due to a change in the internal structure of the fluid (Ghannam et al, 2012;Mortazavi-Manesh and Shaw, 2014) that causes a decrease in viscosity. For this reason, the oil viscosity without NPs is lower than at low shear rates, and although the NPs have an effect at any shear rate, its performance is slightly lower.…”
Section: Resultsmentioning
confidence: 99%
“…The solvation constant (K) decreases as the shear rate increases, due to an increase in the fluidity of crude oil as its rheological behavior is pseudo-plastic or shear thinning (Kee et al, 1988;Mortazavi-Manesh and Shaw, 2014). The shape factor V depends significantly on the geometric shape of asphaltene-NP.…”
Section: Resultsmentioning
confidence: 99%
“…Hysteresis loop tests were carried out to evaluate the viscosity reduction durability over time after the addition of the carrier fluid and nanofluid. According to Mortazavi-Manesh and Shaw [60], the hysteresis flow curves demonstrates thixotropic behavior in the evaluated fluids, which is related with its internal structure breakage and build-up loop and further stability or susceptibility to stress changes.…”
Section: Hysteresis Loop Testsmentioning
confidence: 94%
“…The thixotropic characteristic can be identified and measured by the transient stress techniques such as hysteresis loop and creep experiment. The study of Mortazavi-Manesh and Shaw (2014) shows that the magnitude of thixotropic characteristic of the Maya crude oil become larger as the temperature decreased, and the relationship between thixotropy and temperature can be expressed by the hysteresis loop area and the stress decay. By studying the apparent viscosity of thixotropic liquid, Escudier and Presti (1996) concluded that the apparent viscosity in pipe flow is far from structural equilibrium and always lower than the corresponding value obtained from the rheometer.…”
Section: Introductionmentioning
confidence: 99%